World Class Universities A Contested Concept - Rider, Sharon; Peters, Michael A.; Hyvönen, Mats; Besley, Tina (Evaluating Education: Normative Systems and Institutional Practices, 2020)
This open access book focuses on the dimensions of the discourse of 'The World Class University', its alleged characteristics, and its policy expressions. It offers a broad overview of the historical background and current trajectory of the world-class-university construct. It also deepens the theoretical discussion, and points a way forward out of present impasses resulting from the pervasive use and abuse of the notion of "world-class" and related terms in the discourse of quality assessment. The book includes approaches and results from fields of inquiry not otherwise prominent in Higher Education studies, including philosophy and media studies, as well as sociology, anthropology, educational theory. The growing impact of global rankings and their strategic use in the restructuring of higher education systems to increase global competitiveness has led to a 'reputation race' and the emergence of the global discourse of world class universities. The discourse of world class universities has rapid uptake in East Asian countries, with China recently refining its strategy. This book provides insights into this process and its future development.